Pengaruh Media Audio Visual terhadap Kemampuan Menulis Cerpen pada Siswa Kelas IV di SD Negeri 195 Palembang - Fio Delvina Aldama; Bambang Hermansah; Mega Prasrihamni (Journal on Education, 2023)
The problem encountered in the study was that the lack of ability in short story writing skills in grade IV students at SD Negeri 195 Palembang properly. This study aims to determine the effect of using audio-visual media on the ability to write short stories in grade IV students at SD Negeri 195 Palembang. The type of research used is experimental and using a one-group pretest-protest design experiment. The population of this research is SD Negeri 195 Palembang. The sample in this study was fourth grade students at SD Negeri 195 Palembang with a total of 23 students. Collection techniques in this study using tests. The instrument used is the short story writing test. The criterion for success in this research is what if the minimum average value is 76. Data analysis techniques are processed by hypothesis testing and t-test. Based on the results of the analysis conclusions show that there is a significant effect of the use of audio-visual media on the ability to write short stories in grade IV students at SD Negeri 195 Palembang, with a tcount of 3.689 > ttable of 2.079. So it can be concluded that there is an influence in the use of audio-visual media in short story writing skills in class IV elementary school students.